The Islamic Characters in Teaching English - Sefti Dedek Kendiani (Universitas Bengkulu, 2020)
This study aims to determine the Islamic character implemented by the English Tadris lecturer in the learning process in the English Tadris Study Program at IAIN Curup. The method used was descriptive quantitative by using inferential percentage formula. The sample of this research is 127 students taken from the total number of English Tadris students, 234 students using the Hery King homogeny. The results of this study indicate the first 60.6% of lecturers implement religious aspects of greeting is Islam such as “Assalamualaikum, bismillahirrohmanirrohim, alhamdulillahirrobilalamin, in starting and ending lessons. Second, 48.8% of the lecturers implements aspects the lecturer uses clothes according to the Institut Agama Islam Negeri (IAIN) Curup code of ethics. Third, 47.2% in aspect Appreciating Achievement, the statement used is that the lecturer gives high motivation to students to continue learning. Fourth, 44.2% in democratic aspect, and statement of this aspect namely lecturers are open in accepting student opinions. Fifth,43.3% is the spirit of nationality aspect, the statements in this aspect are the lecturers commemorate national (Indonesian Independence day, Heroes day, mother's day, etc) and Islamic day (Maulid of the Prophet Muhammad SAW, Halal bi halal, Islamic Miraj, Islamic new year).